(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Organs donated for transplantation remain a scarce resource in Switzerland. One of the reasons for this situation is the high percentage of patients or families who refuse to consent to donation. This study aimed to provide an overview of attitudes towards organ donation among Swiss residents, including any intention to donate organs after death, and whether they had already declared their wish and/or communicated it to anyone. METHODS A representative poll investigating the attitude of the Swiss population towards deceased organ donation was conducted between 16 and 28 March 2015. Survey data were collected in 1000 structured telephone interviews. Participants consisted of residents aged 15 years and over from all Swiss regions, and covering the German, French and Italian language areas. RESULTS Of the 1000 survey participants, 92% stated that they have a very positive (58%) or quite positive (33%) attitude towards organ donation, while 6% have a very negative (2%) or quite negative (4%) view. Some 81% of respondents said that they would be willing to donate their organs after death, and 9% expressed a wish not to become a donor. A total of 53% of participants said that they had already communicated or documented whether they wish to donate. CONCLUSION Our study highlights the importance of continuing to raise awareness about the importance of communicating wishes, both in written form and to family members, and suggests that more work is needed to reap the benefits of the substantial support for organ donation among the Swiss population.